Implementations and challenges of online learning in Kayong Utara schools - Dedi Irwan (IKIP PGRI Pontianak, 2023)
This study aims to describe online learning practices in Kayong Utara Regency during the Covid-19 Pandemic. This study used a descriptive qualitative approach. Data collection used semi-structured interviews, with interview tools using interview guidance. This study involved 3 public schools, each school has 5 informants consisting of 1 school leader, 2 English teachers, and 2 students. The researcher used Thematic Analysis and Cross-Case Analysis as data analysis techniques. The results showed that there are 1 school that implements online learning, 1 school that implements hybrid learning, namely offline and online modes, and 1 school that implements offline learning. Implement online learning using applications such as Google Classroom, WhatsApp, Youtube, and Zoom. The challenge faced in designing online learning is the limitation of teachers' ability to use online learning applications. The potential for future improvements is to hold online workshops for teachers, a collaboration between teachers and parents in supervising their children, and infrastructure development to implement online learning in North Kayong Regency.